The role of oxygen and hydroxyl support species on the mechanism of H2 production in the steam reforming of phenol over metal oxide-supported-Rh and -Fe catalysts - Polychronopoulou, Kyriaki; Costa, Costas; Efstathiou, A. M. (My University, 2006)
The aim of this work was to probe for the first time the back-spillover of labile O and OH species during steam reforming of phenol towards H2 production over Rh and Fe supported on MgO, Mg-Ce-O and Mg-Ce-Zr-O metal oxides. This was made possible through SSITKA and other transient isotopic experiments (use of D2O and 18O2). The size of the active pool of H-containing species (H and/or OH) present under reaction conditions as a function of reaction T and catalyst composition, and deuterium kinetic isotope effects were measured.
Keywords: Hydrogen production; Kinetic isotope effect; OH spillover; Oxygen spillover; Phenol; SSITKA; Steam reforming